Primary pulmonary hypertension and fenfluramine use. Issue 6 (December 1993) - Brenot, F; Herve, P; Petitpretz, P; Parent, F; Duroux, P; Simonneau, G
Abstract : Not all the risk factors for primary pulmonary hypertension (PPH) are known. Appetite suppressants, including fenfluramine derivatives, are strongly suspected aetiological agents. In a 5 year retrospective study fenfluramine use was evaluated among patients referred to a medical centre specialising in the management of PPH. Fifteen (20%) of 73 patients with PPH had used fenfluramine: all of them were women and in 10 (67%) there was a close temporal relation between fenfluramine use and the development of exertional dyspnoea. Initial right heart catheterisation in the 15 women showed severe resting pulmonary hypertension (mean (SD)) with pulmonary artery pressure (PAP) 57 (9) mm Hg, cardiac index 2.1 (0.5) l/min/m2, and pulmonary vascular resistance (PVR) 29 (10) U/m2. Short-term epoprostenol infusion produced a significant vasodilator response in 10 patients (mean fall in PVR 24 (15%) compared with control values). Three fenfluramine users with PPH showed spontaneous clinical and haemodynamic improvement 3, 6 and 12 months after drug withdrawal but there was no significant difference in overall survival (transplant recipients excluded) between fenfluramine users and controls. Histological examination of lung tissue from five women who had used fenfluramine and 22 controls, with PPH showed features typical of advanced plexogenic pulmonary arteriopathy in all. These results do not accord with earlier reports that PPH associated with fenfluramine is less severe and has a better outcome. Fenfluramine may be one aetiological agent that can precipitate or hasten the development of PPH. The results of a European case-control study should give new insights into risk factors for PPH and the cause and effect relation with fenfluramine.